Evaluasi Penggunaan Artificial Intelligence dalam Audit Forensik Pada Pandangan Mahasiswa dan Praktisi Akuntansi Tahun 2020-2025 - Pasaribu, Marsel; Harry Z Soeratin (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Abstract: This study aims to disseminate the use of Artificial Intelligence (AI) in forensic audits from the perspective of accounting students and practitioners in Indonesia in 2020-2025. The method used in this study is qualitative analysis with data collection through interviews and surveys of relevant respondents. The results of the study indicate that the use of AI can improve the efficiency and effectiveness of the audit process, as well as help in identifying anomalies and suspicious patterns in financial statements. However, there are challenges in implementing this technology, including the need for better training and understanding of AI among auditors. This study provides recommendations for improving the integration of AI in forensic audit practices in Indonesia.